Philippine rice trade liberalization: Impacts on agriculture and the economy, and alternative policy actions - Perez, Nicostrato D.; Pradesha, Angga (International Food Policy Research Institute, 2019)
Quantitative restriction (QR) on rice import has been a longstanding instrument of the Philippine government that regulated the importation of rice, protected rice farmers and supported the drive for rice self-sufficiency of the country. However, with the pas-sage of the Republic Act No. 11203 or the Philippine rice trade liberalization law in February 2019, the QR was lifted and replaced with import tariffs instead. This policy shift can have far-reaching impacts not only to rice and agriculture but to the entire economy and to the global rice market as well - with important implications to the general welfare, nutrition and food security of the country. Hence, an ex-ante impact assessment study aimed at simulating, quantifying and understanding the effects of rice liberalization on farmers, consumers and various stakeholders can assist the government in proactively crafting and putting in place appropriate investment and policy interventions, while transitioning from QR and moving toward longer-term rice and food security.